The Correlation between Hygiene Habit and Body Mass Index of Healthy People - Swanny Trikajanti Widyaatmadja; Young-Duk Kim; Kyeonghwa Byun (Postgraduate, University of Mataram, 2024)
We investigated to find out the BMI of healthy people and the relation to their health environmental habits. We surveyed walking travelers’ participants who had hiking experiences in South Korea. We also analyzed the BMI classification by hand hygiene habits, shoe washing and garbage disposal maintaining for distribution BMI features. The survey was conducted through an online questionnaire. The subjects included 569 adult participants, males and females aged 20 years and older. Box plot visualization and cross-tab test were used for analysis. The results revealed that almost 48.5% of all participants handwash before meals. Statistically, it showed a significant relationship between normal calcified BMI and washing hands before eating (p-val : 0.001) and before eating snacks (p-val : 0.000). The distribution of participants who were in BMI classification of overweight (BMI 24.9 29.9) in a group that had habits of washing hands before meals when traveling showed 10% lower. The lower the number of cleaning frequencies, increasing the higher BMI. However, the impact on shoe care (washing) and waste care was negligible. The result shows that good habits in the environment, especially hand hygiene, influence the BMI. This indicates that certainty about health and some health environmental habits also affect health.